Toward a phylogeny of Maxillariinae orchids: multidisciplinary studies with emphasis in Brazilian species - Singer, Rodrigo B. (Universidad de Costa Rica, 2016)
It has been demonstrated that the neotropical sub- tribe Maxillariinae comprises a well-supported mono- phyletic orchid group, according to cladistic analyses of nuclear and chloroplast DNA regions